2003
DOI: 10.1046/j.1440-1584.2003.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Injury in Indigenous Australians Admitted to Cairns Base Hospital

Abstract: Personal injury costs are high in the indigenous community, in human and material terms. More resources should be directed towards injury prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Similar results have been found for females living in First Nations communities in Ontario, 11 and indigenous females in Queensland, Australia. 28 In this study, we found higher rates of selfinflicted injury hospitalization in highpercentage Aboriginal-identity areas, with poisoning, cutting/piercing and drowning/suffocation being the three leading causes of hospitalization. Rates of selfinflicted injury hospitalization were higher for females than males, and rates were highest for males and females living in high-percentage Inuit-identity areas.…”
Section: Discussionmentioning
confidence: 59%
“…Similar results have been found for females living in First Nations communities in Ontario, 11 and indigenous females in Queensland, Australia. 28 In this study, we found higher rates of selfinflicted injury hospitalization in highpercentage Aboriginal-identity areas, with poisoning, cutting/piercing and drowning/suffocation being the three leading causes of hospitalization. Rates of selfinflicted injury hospitalization were higher for females than males, and rates were highest for males and females living in high-percentage Inuit-identity areas.…”
Section: Discussionmentioning
confidence: 59%
“…MacIntosh and Pearson recently compared orthopaedic trauma presenting to Cairns Base Hospital between indigenous and nonindigenous populations. 22 They looked at injuries often caused by the perpetrators of mandibular fractures in our community, for example tooth-knuckle injuries. They similarly found that a disproportionate number of such injuries (23%) occurred in the indigenous population.…”
Section: Access To Health Carementioning
confidence: 99%
“…By comparison, the landmark trauma epidemiology study by Kuhn et al 5 of 11 320 eyes from the United States Eye Injury Registry (USEIR) reported 19.5% of ocular trauma resulted from assault. The link between Indigenous status, remote living and interpersonal‐violence has been well documented both in FNQ 6,24 and the broader Australian community 25‐28 . Injuries resulting from inter‐personal violence represent the greatest disparity in hospitalization rates between Indigenous and non‐indigenous people 25 .…”
Section: Discussionmentioning
confidence: 99%